Pulse-Spray Pharmacomechanical Thrombolysis of Native Arteriovenous Fistulas and Grafts under Ultrasound Guidance: Our Initial Experience - Praveen Kumar Vasanthraj; Varun Kumar Bandi; Venkata Sai; Manikanthan Shekar (Journal of Clinical Interventional Radiology ISVIR)
Chronic renal diseases have been on rise with most patients requiring renal transplantation. With advances in treatment, patients undergo hemodialysis through arteriovenous (AV) fistulas and grafts. Thrombosis in these fistulas and grafts are more common and may result in failure. Interventional radiology plays an important role in managing these thromboses through catheter-directed thrombolysis. With success rate of more than 80%, catheter-directed thrombolysis has become the treatment of choice. However, the need of trained personnel, well-equipped catheter laboratories, and expensiveness are its disadvantages. We share our initial experience in two patients in whom we have performed ultrasound-guided percutaneous pulse-spray pharmacomechanical thrombolysis as a day-care procedure. This technique is less expensive, can have a wider outreach, and patients can be benefitted early to avoid new access.